Prophage Excision in Streptococcus pneumoniae Serotype 19A ST320 Promote Colonization: Insight Into Its Evolution From the Ancestral Clone Taiwan 19F-14 (ST236) - Chen, Yi-Yin; Wang, Jin-Town; Lin, Tzu-Lung; Gong, Yu-Nong; Li, Ting-Hsuan; Huang, Ya-Yu; Hsieh, Yu-Chia (Frontiers in Microbiology, 2019)
Streptococcus pneumoniae 19A ST320, a multidrug-resistant strain with high disease severity that notoriously spread before the use of expanded pneumococcal conjugate vaccines, was derived from a capsular switching event between an international strain Taiwan 19F-14 (ST236) and a serotype 19A strain. However, the molecular mechanisms underlying the adaptive evolution of 19F ST236 to 19A ST320 are unknown. In this study, we compared 19A ST320 to its ancestral clone, 19F ST236, in terms of adherence to respiratory epithelial cells, whole transcriptome, and ability to colonize a young mouse model. Serotype 19A ST320 showed five-fold higher adherence to A549 cells than serotype 19F ST236. High-throughput mRNA sequencing identified a prophage region located between dnaN and ychF in both strains; however, the genes in this region were expressed at significantly higher levels in 19A ST320 than in 19F ST236. Analysis by polymerase chain reaction (PCR) showed that the prophage is able to spontaneously excise from the chromosome and form a circular episome in 19A ST320, but not in 19F ST236. Deletion of the integrase in the prophage of 19A ST320 decreased spontaneous excision and cell adherence, which were restored by complementation. Competition experiments in mice showed that the integrase mutant was six-fold less competitive than the 19A ST320 parent (competitive index [CI]: 0.16; p = 0.02). The 19A ST320 prophage-deleted strain did not change cell adherence capacity, whereas prophage integration strains (integrase mutant and 19F) had decreased expression of the down-stream ychF gene compared to that of 19A ST320. Further deletion of ychF significantly reduced cell adherence. In conclusions, these findings suggest that spontaneous prophage induction confers a competitive advantage to virulent pneumococci.